2022
DOI: 10.1101/2022.03.26.485922
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unique molecular signatures sustained in circulating monocytes and regulatory T cells in Convalescent COVID-19 patients

Abstract: Over two years into the COVID-19 pandemic, the human immune response to SARS-CoV-2 during the active disease phase has been extensively studied. However, the long-term impact after recovery, which is critical to advance our understanding SARS-CoV-2 and COVID-19-associated long-term complications, remains largely unknown. Herein, we characterized multi-omic single-cell profiles of circulating immune cells in the peripheral blood of 100 patients, including covenlesent COVID-19 and sero-negative controls. The red… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…Those subjects exhibited a higher Treg frequency than severely ill who were categorized as having high CD8 + T cell counts (>250/ml) and patients with mild initial disease (63). Two other studies that investigated total Treg frequencies documented both higher and lower proportions in convalescent outpatients compared to those who were hospitalized (51, 59) (Figure 3). Similarly as heterogeneous were the results of the studies that investigated Treg subsets.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…Those subjects exhibited a higher Treg frequency than severely ill who were categorized as having high CD8 + T cell counts (>250/ml) and patients with mild initial disease (63). Two other studies that investigated total Treg frequencies documented both higher and lower proportions in convalescent outpatients compared to those who were hospitalized (51, 59) (Figure 3). Similarly as heterogeneous were the results of the studies that investigated Treg subsets.…”
Section: Resultsmentioning
confidence: 83%
“…The trend towards a quantitative reconstitution of Tregs was supported by five studies investigating patients recovering from diseases of different severity (51,52,54,55,59). The fact that the studies were not able to find significant differences in Treg frequency between recovering subjects and seronegative controls suggests that the peripheral Treg population was either unaffected by the initial disease or returned to normal values within the first six weeks following mild disease (54,55,59) or four months following severe disease (51,59).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Under normal conditions, Foxp3 + Tregs migrate into inflamed tissues to suppress inflammatory responses to exert immunosuppressive effects and accelerate tissue repair [ 15 , 138 ]. In pre-existing respiratory comorbidities such as COVID-19, which leads to the disruption of the immune system, exacerbated inflammation which is partly due to the decreased expression of Tregs or defects in these cells results in weakening the Tregs effects of inflammatory inhibition, causing an imbalance in Treg/Th17 ratio, and increasing the risk of respiratory failure [ 137 , 139 , 140 , 141 ]. Since our data showed that the smoke and morphine combination promote weakened, plastic/dysfunctional Tregs and Treg plasticity toward Th17 cells, smoke plus morphine in combination in pre-existing respiratory co-morbidities such as COVID-19 will exacerbate inflammation and increase the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%